2021
DOI: 10.24969/hvt.2021.269
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of cTnT/CK-MB ratio is as a predictor of change in cardiac function after myocardial infarction

Abstract: Objective: Cardiac enzymes that are released during acute myocardial infarction (AMI) are of prognostic importance. This study aimed to investigate the relationship between cardiac troponin T (cTnT) and creatine kinase myocardial band (CK-MB) release during AMI and 6-month post-AMI left ventricular (LV) function, as assessed by magnetic resonance imaging. Methods: This prospective cohort observational study included 131 adult patients (113 males, 18 females, mean age 53.8 (8.6) years) who had been diagnosed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…CK-MB, although less specific, remains a useful marker for diagnosing AMI, especially in conjunction with troponins (Aydin et al, 2019). The CK-MB/Troponin ratio has shown diagnostic efficacy and prognostic value in assessing left ventricular activities post-STEMI (Eyyupkoca et al, 2021). Myoglobin, despite lacking specificity, is sensitive for early MI detection and exclusion (Asl and Rahimzadegan, 2022).…”
Section: Biochemical Markers Role and Potential Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…CK-MB, although less specific, remains a useful marker for diagnosing AMI, especially in conjunction with troponins (Aydin et al, 2019). The CK-MB/Troponin ratio has shown diagnostic efficacy and prognostic value in assessing left ventricular activities post-STEMI (Eyyupkoca et al, 2021). Myoglobin, despite lacking specificity, is sensitive for early MI detection and exclusion (Asl and Rahimzadegan, 2022).…”
Section: Biochemical Markers Role and Potential Mechanismmentioning
confidence: 99%
“…The cTnT/CK-MB ratio may perform diagnostically more effectively than cTnT and CK-MB by themselves. In clinical practice, the cTnT/CK-MB ratio can be utilized for risk classification and therapy optimization (Eyyupkoca et al, 2021).…”
Section: Biochemical Markers Role and Potential Mechanismmentioning
confidence: 99%
“…The latter constitutes a high percentage of cases with the increased enzyme (8). A recent analysis of studies in large groups of patients has shown that enzyme release is more common than previously thought and is also associated with prognosis (9)(10)(11). According to findings in essential databases, patients with increased cardiac markers had higher complications and cardiac mortality, independent of other predictors of mortality (12).…”
Section: Introductionmentioning
confidence: 99%